Evidence for a primary autoimmune type of diabetes mellitus. Issue 6147 (4th November 1978) - Bottazzo, G F; Cudworth, A G; Moul, D J; Doniach, D; Festenstein, H
Abstract : Sixty-eight patients with longstanding diabetes and persistent islet-cell antibody and 35 with coexistent diabetes and Graves's disease or primary myxoedema were studied with particular reference to the HLA system and autoantibody patterns. A higher incidence of HLA-B8 than normal was observed in the two groups. An additive relative risk exists when type I diabetes and autoimmune thyroid disease coexist, indicating that different HLA-linked genes may confer susceptibility to the pancreatic and thyroid disorders. Other characteristics, including female predominance, a later onset of diabetes, and a strong family history of autoimmune endocrinopathy, provide further evidence that this form of diabetes is aetiologically distinct from that generally seen in children. These results support the hypothesis of a primary autoimmune type of diabetes mellitus.